2014
DOI: 10.1590/s1413-70542014000600007
|View full text |Cite
|
Sign up to set email alerts
|

Corn germ meal as substitute for corn in the diet of confined Santa Inês sheep: chemical and lipid meat composition

Abstract: The per capita consumption of sheep meat in Brazil is still small compared to meat originating from other animal species, the lipid profile of meat named as responsible for reduced consumption. Despite the influence of sex, breed, weight at slaughter and environment, diet is seen as a major factor influencing the lipid composition of sheep meat. This study evaluated the effect of replacing corn by corn germ meal (0, 25, 50, 75 and 100%) in the diet of Santa Inês sheep on the meat's chemical and lipid composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…The concentration of C18:2 n-6 was high in the WCG used in the experimental diets, and a part of this fatty acid, in the materials’ matrix, may have escaped from ruminal biohydrogenation [ 57 ]. This result is in agreement with the report of Urbano et al [ 8 ], who mentioned higher levels of C18:2 n-6 and CLA (C18:2 9c 11t) fatty acids in the lambs’ meat when animals were fed diets with total replacing of ground corn by WCG.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The concentration of C18:2 n-6 was high in the WCG used in the experimental diets, and a part of this fatty acid, in the materials’ matrix, may have escaped from ruminal biohydrogenation [ 57 ]. This result is in agreement with the report of Urbano et al [ 8 ], who mentioned higher levels of C18:2 n-6 and CLA (C18:2 9c 11t) fatty acids in the lambs’ meat when animals were fed diets with total replacing of ground corn by WCG.…”
Section: Discussionsupporting
confidence: 93%
“…The WCG has been studied in diets for ruminants due to its crude protein (10 to 15%) [ 5 , 6 ], ether extract (44%) [ 1 ], and linoleic acid (56% of total fatty acids) contents [ 1 ]. The inclusion of WCG in the ruminant diets aims to increase energy density [ 7 ] and polyunsaturated fatty acids, to obtain higher levels of conjugated linoleic acid (CLA) in the meat, which are beneficial to human health [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nutritional management is one of the main factors that affect the quantity and quality characteristics of the carcass and meat [ 39 ]. In this study, no influence of the inclusion of fat sources in the diets was observed on the physicochemical characteristics of the carcass or centesimal composition of the LL muscle, which is in agreement with several studies in this area [ 40 , 41 , 42 ].…”
Section: Discussionsupporting
confidence: 93%
“…Dry environments, such as the semi-arid region of the Brazilian Northeast, represent many challenges to produce ruminants, mainly due to fluctuations in forage production caused by limiting climatic conditions, such irregular rainfall. In this context, spineless cactus (SC) is a strategic feed option, being a forage crop rich in water and non-fibrous carbohydrates (Silva et al, 2021). However, the need to combine this cactus with sources of physically effective fiber and nitrogen is already well established.…”
mentioning
confidence: 99%